Bisdemethoxycurcumin and Its Cyclized Pyrazole Analogue Differentially Disrupt Lipopolysaccharide Signalling in Human Monocyte-Derived Macrophages - Serena Tedesco; Morena Zusso; Laura Facci; Annalisa Trenti; Carlotta Boscaro; Federica Belluti; Gian Paolo Fadini; Stephen D. Skaper; Pietro Giusti; Chiara Bolego; Andrea Cignarella (Mediators of Inflammation)
Several studies suggest that curcumin and related compounds possess antioxidant and anti-inflammatory properties including modulation of lipopolysaccharide- (LPS-) mediated signalling in macrophage cell models. We here investigated the effects of curcumin and the two structurally unrelated analogues GG6 and GG9 in primary human blood-derived macrophages as well as the signalling pathways involved. Macrophages differentiated from peripheral blood monocytes for 7 days were activated with LPS or selective Toll-like receptor agonists for 24 h. The effects of test compounds on cytokine production and immunophenotypes evaluated as CD80+/CCR2+ and CD206+/CD163+ subsets were examined by ELISA and flow cytometry. Signalling pathways were probed by Western blot. Curcumin (2.5–10 μM) failed to suppress LPS-induced inflammatory responses. While GG6 reduced LPS-induced IκB-α degradation and showed a trend towards reduced interleukin-1β release, GG9 prevented the increase in proinflammatory CD80+ macrophage subset, downregulation of the anti-inflammatory CD206+/CD163+ subset, increase in p38 phosphorylation, and increase in cell-bound and secreted interleukin-1β stimulated by LPS, at least in part through signalling pathways not involving Toll-like receptor 4 and nuclear factor-κB. Thus, the curcumin analogue GG9 attenuated the LPS-induced inflammatory response in human blood-derived macrophages and may therefore represent an attractive chemical template for macrophage pharmacological targeting.